Rosja oczami ekscentryka, czyli Moskwa–Pietuszki Wieniedikta Jerofiejewa w kontekście mechanizmów reifikacji - Waligórska-Olejniczak, Beata (Przegląd Rusycystyczny, 2011)
РОССИЯ ГЛАЗАМИ ЭКСЦЕНТРИКА ИЛИ МОСКВАПЕТУШКИ ВЕНЕДИКТА ЕРОФЕЕВА В КОНТЕКСТЕ МЕхАНИЗМОВ РЕИФИКАЦИИ Резюме Автор статьи концентрируется на анализе образа советской действительности в поэме Москва–Петушки с точки зрения отношений человек–вещь. Текст обращает внима-ние на примеры механизмов овеществления, функционирующих в художественном мире Ерофеева, которые можно связать с категориями реификации: тотализирующей, манипулятивной, эксплуатационной и неантизирующей. Особое место в дискуссии занимает исследование бинарных опозиций типа: духовое–телесное, открытое–за-крытое, определяющих как логику тоталитарного режима, так и трагизм человеческой экзистенции эпохи постмодернизма. RUSSIA THROUGH THE EYES OF AN ECCENTRIC, OR MOSCOW–PETuSHKI BY VENEDICT EROFEEV IN THE CONTEXT OF MECHANISMS OF REIFICATION Summary The article concentrates on the analysis of pathological Soviet reality represented in the lyrical poem Moscow–Petushki from the point of view of the relationship between a human being and an object. The author focuses on the mechanisms of reification utilised in the artistic world of V. Erofeev categorising them as the examples of totalizing, manipulative, practical and neantising types of the above mentioned phenomenon. The author pays particular attention to the studies of binary oppositions such as spiritual-corporeal or exposed-hidden, which define logic of the totalitarian system as well as tragism of the human existence in the era of post-modernity